PENGARUH CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK BELIKOPI DI MERR PANDUGO SURABAYA DENGAN WORD OF MOUTH SEBAGAI VARIABEL MEDIASI - Yayang Pitino; Endah Budiarti (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research aims to evaluate the impact of brand image and promotion on purchasing decisions for Belikopi products at Merr Pandugo Surabaya. The word-of-mouth variable is the mediator in this research. A total of 100 respondents who had purchased and tasted Belikopi products in Surabaya participated in data collection through questionnaires. The method used to analyze this research is Structural Equation Modeling (SEM) with the application of the Partial Least Squares (PLS) mediation test tool to test the relationship between variables in the conceptual framework that has been prepared.